Improving Interaction Ability in Social Isolation Patients by Application of Group Activity Therapy - Suhanda Suhanda; Andan Firmansyah; Lidia Naela Sangadah (Jurnal Vocational Nursing Sciences (VNUS), 2022)
Objective: To find out the description of nursing care giving group activity therapy socialization: Ability to introduce oneself, ability to make acquaintances, and ability to overcome social isolation and withdrawal disorders in schizophrenic patients at BLUD RSU Banjar City Method: This study uses a qualitative descriptive method with a case study approach. The author takes one client as the subject of a case study that fits the inclusion and exclusion criteria. The author collects data by means of observation and documentation. The focus of the intervention is to use group activity therapy interventions. Results: The results of the case studies at the review stage showed that they did not want to meet many people, the client's eye contact was lacking, and there was no interaction with fellow patients in the passive ward. The intervention used in this case study is a strategy of implementing social isolation with a focus on social interaction skills. The focused intervention used is the application of social isolation group activity therapy. Conclusion: During the three-meeting intervention, there was a change in social interaction skills, both in the ability to introduce oneself, the ability to make acquaintances, and the ability to converse, from a score of 0 to a score of 4.